2016
DOI: 10.1364/boe.7.004154
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of spatial frequency domain imaging (SFDI) for optically characterizing a preclinical oncology model

Abstract: Determination of chemotherapy efficacy early during treatment would provide more opportunities for physicians to alter and adapt treatment plans. Diffuse optical technologies may be ideally suited to track early biological events following chemotherapy administration due to low cost and high information content. We evaluated the use of spatial frequency domain imaging (SFDI) to characterize a small animal tumor model in order to move towards the goal of endogenous optical monitoring of cancer therapy in a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 50 publications
1
58
0
1
Order By: Relevance
“…The choice of SFDI f x pairs affects both the depth sensitivity of SFDI (as demonstrated in the previous section), as well as the ability to accurately extract optical properties . To assess tradeoffs between these two factors, we quantified optical property uncertainties for DC and 0.1 mm −1 , and 0.05 and 0.1 mm −1 given that the former has been identified as a f x pair that minimizes optical property extraction errors , and the latter was found to provide good agreement in depth sensitivity between SFDI and MPM. We found that there was good agreement in extracting optical properties between the two spatial frequency pairs for a range of optical properties (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…The choice of SFDI f x pairs affects both the depth sensitivity of SFDI (as demonstrated in the previous section), as well as the ability to accurately extract optical properties . To assess tradeoffs between these two factors, we quantified optical property uncertainties for DC and 0.1 mm −1 , and 0.05 and 0.1 mm −1 given that the former has been identified as a f x pair that minimizes optical property extraction errors , and the latter was found to provide good agreement in depth sensitivity between SFDI and MPM. We found that there was good agreement in extracting optical properties between the two spatial frequency pairs for a range of optical properties (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, we have shown in a previous study that spatial frequency domain imaging (SFDI) can be used to monitor the in vivo tumor state of a subcutaneous tumor xenograft model grown in mouse over a period of 45 days. 11 SFDI is a widefield DOI modality, capable of tracking the same noninvasive and label-free metrics measured using clinical DOI modalities and is well suited for preclinical oncology work given its shallower penetration depth (typically mm). 11,12 Much of the prior published works using SFDI for both small animal and clinical research have utilized the assumption of homogeneity in depth when extracting optical properties from tissue.…”
Section: Introductionmentioning
confidence: 99%
“…11 SFDI is a widefield DOI modality, capable of tracking the same noninvasive and label-free metrics measured using clinical DOI modalities and is well suited for preclinical oncology work given its shallower penetration depth (typically mm). 11,12 Much of the prior published works using SFDI for both small animal and clinical research have utilized the assumption of homogeneity in depth when extracting optical properties from tissue. [13][14][15][16] For example, in our prior preclinical monitoring study, we modeled mouse tumor tissue as a semi-infinite homogeneous medium and used the results of a Monte Carlo (MC) simulation to create a look-up-table (LUT) inversion algorithm to recover optical property estimates from SFDI measurements of diffuse reflectance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SFDI techniques have been utilized widely to characterize tissue composition and function in humans, 3,4 animal models, and ex vivo tissue specimens. 5,6 There is generally a tradeoff between spectral and spatial information content in SFDI instruments. This is due to the fact that wide-field imaging is typically performed serially at several discrete wavelengths using selective illumination and/or optical filters.…”
Section: Introductionmentioning
confidence: 99%